Analysis of different domains of physical activity with health-related quality of life in adults: 2-year cohort - Scarabottolo, Catarina Covolo [UNESP] (2022)
Background: It is estimated that, worldwide, 9% of deaths occur as a result of insufficient physical activity (PA) practice. Practicing PA can prevent and/or reduce the deleterious effects of different types of diseases and can improve general health aspects related to health-related quality of life (HRQoL). Purpose: To analyze the relationship of different PA domains with different HRQoL domains over a two-year period. Methods: This is an observational study with a two-year longitudinal design. The sample, composed of adults, was selected from a randomization of the streets of the different regions (north, south, east, west and center) covering individuals from all areas of the city. To assess the practice of PA, the Baecke questionnaire was used. The instrument Medical Outcomes Study SF-36-Item Short Form Health Survey was used to assess the HRQoL domains. Linear regression models were used to analyzed the association of different PA domains with changes in HRQoL. Multivariate statistical models were adjusted for gender, age, socioeconomic status, marital status, the respective PA score at baseline, smoking, body mass index, and morbidity. Results: 331 adults were evaluated. There was a decrease in the practice of PA in the occupational domain and an increase in the leisure/locomotion domain. Regarding HRQoL, there was an increase in the scores of body pain and mental health, and a decrease in scores of general health, vitality, social aspects and emotional aspects. The PA practice in the occupational domain was inversely related to functional capacity (β = − 7.2 [CI 95% − 13.0; − 1.4]). The practice of PA through sports in leisure time was positively associated with vitality (β = 5.5 [CI 95% 0.2; 10.7]) and mental health (β = 15.2 [CI 95% 6.8; 23.7]). PA practice during leisure and locomotion was inversely associated with functional capacity (β = − 5.68 [CI 95% − 10.7; − 0.6]) and positively associated with vitality β = 4.8 [CI 95% 0.8; 8.7]) and mental health (β = 8.4 [CI 95% 2.0; 14.9]). The total PA practice was inversely associated with functional capacity (β = − 3.8 [CI 95% − 6.5; − 1.2]) and positively associated with pain in the body (β = 4.9 [CI 95% 0.3; 9.4]), vitality (β = 2.9 [CI 95% 0.7; 5.0]) and mental health (β = 5.7 [CI 95% 2.2; 9.2]). Conclusions: It is suggested that practicing PA continuously within a period of two years can positively affect some physical aspects and some mental aspects related to HRQoL, but not all of them. A strategy for public policy actions is to explore these variables by domain and thus detect the real needs and improvements that can be made for the population.